New Zealand : outlier of the five eyes? - Schleich, Anne-Marie (2021)
With the US-China strategic competition intensifying, New Zealand navigates these tricky geopolitical waters and pursues it’s ‘independent’ foreign policy even at the risk of offending its Five Eyes partners.